The Effects of Notary Code Breaking In Publication or Self Promotion in Pangkalan Bun - Ismi Hardiyanti; Aris Sophian; Achmad Sulchan (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2020)
The purpose of this study was to: 1) to assess and analyze the legal consequences for a notary public notary who violate the code of conduct in doing publicity or self-promotion on the base bun. 2) to assess and analyze the implementation of Effects Notary The Notary Code Breaking In Doing Publication Or Self Promotion In Pangkalan Bun.Based on the results of data analysis concluded that: 1) In the code of conduct notary was clear in saying that a notary is prohibited from publishing or self-promotion, either individually or jointly, it because may result in the authority and dignity of a notary as a public official downhill , 2) Violation of Implementation notary who violates the provisions of the code of conduct in the form of advertising self notary was his only impact on the position of the Notary as a member of the Association and no impact on the position of the notary as a public official.Key words : Notary Code of Ethics; Self Promotion; Effects.